Effect of Enzyme Type on the Antioxidant Activities and Functional Properties of Enzymatic Hydrolysates from Sea Cucumber (Cucumaria frondosa) Viscera. Issue 6 (17th August 2016) - Yan, Mingyan; Tao, Haiteng; Qin, Song
ABSTRACT: Effects of various proteases were obvious on the amino acid composition, antioxidant activities, and functional properties of enzymatic hydrolysates prepared from sea cucumber viscera (SCV). Alcalase, trypsin, and flavourzyme conferred better antioxidant activities on hydrolysates and endowed them with a higher degree of hydrolysis, coming to 19.08, 32.38, and 15.94%, respectively. For functional properties, neutrase- and flavourzyme-derived hydrolysates showed better foaming properties. Amino acid composition suggested that papain, neutrase, alcalase, and bromelain granted the hydrolysate's high nutritional quality. The results indicated that SCV hydrolysates could be used in food systems to impart desirable characteristics to products.